Comparative evaluations and coordinated control of energy routers - Cui, Chengjin (Nanyang Technological University, 2024)
Energy is a fundamental part of contemporary industries and the basic material of people's lives. However, the current global energy situation confronts many difficulties, such as conventional energy shortages, rising energy consumption, various forms of environmental contamination, climate change, and other issues. Energy Internet was proposed to meet the energy crisis. The development of power electronics, information technology, and communication is the primary driver of Energy Internet promotion. The Energy Router, the central element of Energy Internet, is created and oversees converting energy from one system to another, gathering and exchanging data on power flow, bus voltage, and other things.